Desarrollo del servicio de factoraje financiero para la Cooperativa Imbacoop enfocado a patios de vehículos usados en la ciudad de Otavalo. - Vaca Romero, Edgar Paúl (2014)
For the development of this facility is supported Cooperative Savings and Credit Imbacoop and UPS, who after a thorough analysis of the information after their respective collection and interpretation of results obtained in studies of administrative legal market and financial viability of this project that generated much buzz in the automotive sector in the city of Otavalo that contribute to the development of this sector of the economy is determined. This project will run through the different branches we have in Imbacoop cooperative located in major cities such as: Otavalo, Atuntaqui and Ibarra, taking a fastest growing segment in the economy of our country to provide this financial alternative